Editorial Foreword - Jianbang Deng (IKAT: The Indonesian Journal of Southeast Asian Studies, 2019)
IKAT is a journal cited for Southeast East Asian Studies, and it is also a journal that is based in one of the Southeast Asian countries, in the country of Indonesia. For a long ????me, we understand social forma????on and social changes from socie????es in Southeast Asia relying heavily on journals in the western world. For this reason, it was very welcoming to see that the Center for Southeast Asian Social Studies (CESASS) at the Universitas Gadjah Mada ini????ated an academic journal, taking efforts to contribute the knowledge produc????on of social sciences in Indonesia and beyond. This year the IKAT already celebrated its second birthday.